In vitro characterization on the role of APOE polymorphism in human hippocampal neurogenesis. Issue 4 (28th January 2023) - Lee, Hyunah; Price, Jack; Srivastava, Deepak P.; Thuret, Sandrine
Abstract: Hippocampal neurogenesis (HN) is considered an important mechanism underlying lifelong brain plasticity, and alterations in this process have been implicated in early Alzheimer's disease progression. APOE polymorphism is the most common genetic risk factor for late‐onset Alzheimer's disease where the ε4 genotype is associated with a significantly earlier disease onset compared to the neutral ε3 allele. Recently, APOE has been shown to play an important role in the regulation of HN. However, the time‐dependent impact of its polymorphism in humans remains elusive, partially due to the difficulties of studying human HN in vivo. To bridge this gap of knowledge, we used an in vitro cellular model of human HN and performed a time course characterization on isogenic induced pluripotent stem cells with different genotypes of APOE . We found that APOE itself was more highly expressed in ε4 at the stem cell stage, while the divergence of differential gene expression phenotype between ε4 and ε3 became prominent at the neuronal stage of differentiation. This divergence was not associated with the differential capacity to generate dentate gyrus granule cell‐like neurons, as its level was comparable between ε4 and ε3. Transcriptomic profiling across different stages of neurogenesis indicated a clear "maturation of functional neurons" phenotype in ε3 neural progenitors and neurons, while genes differentially expressed only in ε4 neurons suggested potential alterations in "metabolism and mitochondrial function." Taken together, our in vitro investigation suggests that APOE ε4 allele can exert a transcriptome‐wide effect at the later stages of HN, without altering the overall level of neurogenesis per se.